Vrede i Ludvig Holbergs komedier - Raaby Gammelgaard, Lasse (Slagmark - Tidsskrift for idéhistorie, 2020)
“Ludvig Holberg’s angry comedies” This article contributes to research on anger and neo-classicist comedy drama. Facilitating a dialogue between state-of-the-art theory on anger as a complicated, ambiguous and broad-spectrum emotion and Aristotelian drama theory, especially the concept of anagnorisis, it is argued that neo-classicist comedies are scenes of social interaction that are replete with angry feelings and reactions. Characters are constantly provoking each other and reacting to provocations. The main case is Ludvig Holberg’s comedies. Anger is investigated both from a quantitative perspective employing corpus-linguistic approaches (searching for concordance and clusters in all 36 comedies) and through a close reading of Den Stundesløse.